Vulnerability Assessment of Peoples Exposed to Landslides in Panchase of Nepal using Analytical Hierarchy Process - Bahadur Budha, Padam; Rai, Pawan; Katel, Prem; Khadka, Anu (International Journal of Environment, 2020)
The occurrence of landslides in mountainous areas of Nepal is recurrent phenomena and this can be disastrous if occurred within human settlements. Proper research is required to manage and reduce the risks of the disaster in places where landslides had occurred frequently. In risk assessment estimation of vulnerability is one major component. This research was aimed to generate information on the vulnerability of people in the Panchase area of central Nepal. The method of analytical hierarchy process was used to define the weightage to be assigned for 4 factors and 26 indicators used in the research. 377 households were surveyed with a questionnaire designed to collect information on those indicators. The households sampled for the survey were made sure that they were near or around the landslide affected area. The response for each indicator was converted into scores which when summed up yielded the vulnerability score. This score for each household was used to categorize households into five levels of vulnerability from very low, low, moderate, high, to very high. The numbers of households in each category were 16, 92, 191, 75, and 3 respectively. Environmental and economic indicators were inflicting higher vulnerability in this research location. Remoteness and lesser number of facilities and/or services, lower numbers of governmental offices, absence of banking and financial institutions, lesser preferences for insurances and savings, degraded natural water sources were major determinants of higher vulnerability in Panchase. These indicators should be prioritized during disaster risk management in Panchase.